On the life course perspective in income related health inequalities: a semiparametric approach - Martin Siegel; Karl Mosler (University of Cologne, Seminar of Economic and Social Statistics, 2010)
Compared with the broad supply of literature measuring socioeconomic gradients in the distribution of health, only little is know about the life course perspective regarding income related inequalities. This article combines the reowned concentration index approach with semiparametric estimation techniques to derive a new varying index of inequality that copes without a priori sample stratification. We illustrate the power of this new index using health data drawn from the German microsensus and find support for the age as leveler hypothesis. Our index suggests that significant inequalities to the detriment of the deprived increase over the working life and reacht their maximum around the age for retirement. We find no significant inequalities for adolescents and elder people.
Keywords: 330